2016
DOI: 10.1002/jso.24334
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based comparison of 30‐day readmission after surgery for colon and rectal cancer: How are they different?

Abstract: Overall, 13,571 patients were identified and the readmission rates significantly differed between rectal and colon cancer patients (7.1% colon and 10.7% rectal P = 0.001). Diabetes, age, and discharge to long term care were significantly different among colon and rectal patients in the prediction of readmission. Readmission for renal and stoma causes was more prominent in the rectal cohort. The adjusted cost difference for readmission did not significantly differ between rectal and colon cancer $178 ($1,924-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Our finding of 7.2% of 30-day readmission compares favorably with 10.7% reported by Doumouras e al. [ 29 ] Similar to Schneider et al [ 30 ], we found that the risk of readmission increased across the study periods. In the multivariate analysis, being operated on in more recent time periods independently increased the odds of readmission.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our finding of 7.2% of 30-day readmission compares favorably with 10.7% reported by Doumouras e al. [ 29 ] Similar to Schneider et al [ 30 ], we found that the risk of readmission increased across the study periods. In the multivariate analysis, being operated on in more recent time periods independently increased the odds of readmission.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the proportion of patients having a covering stoma during the study period increased from 31.5% in 2002-2006 to 41.8% in 2011-2014. As postoperative morbidity and stoma-related problems have been found to impact negatively on 30-day readmission [ 29 , 30 ], it is reasonable to explain the increased rates of 30-day hospitalization with the increased use of neoadjuvant treatments and covering stoma. Furthermore, early discharge is thought to have an impact on readmissions; however, several studies found either no impact or an inverse association between LOS and the rate of 30-day readmission [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that rectal cancer is different from colon cancer in aetiology, genetics, anatomy, clinical manifestation, biological feature, treatment response and clinical outcomes 3 6 . Lifestyle factors such as diet, smoking and physical activity have different effects in colon cancer than in rectal cancer 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Once the C statistic was maximized, a scoring index was developed following the methods of Sullivan et al 20 . Because a substantial body of literature is known about the risk of readmissions associated with colorectal surgery for cancer 21,22 , a baseline point value of 1 was assigned to the parameter estimate for the risk associated with cancer as the indication for surgery. The expected probability was calculated using the same method as van Walraven et al, and confidence intervals for observed probabilities were determined using the exact method 10,23 .…”
Section: Discussionmentioning
confidence: 99%